Effect of Eugenia jambolana and Psidium guajava Leaf Meal Mixture Supplementation on Nutrient Utilization, Antioxidant Indices and Immune Responses in Broiler Chicks - Zargar, M. A.; Pathak, A. K.; Sharma, R. K.; Daing, M. I. (Indian Journal of Animal Nutrition, 2020)
Present study was conducted in 120 day-old unsexed broiler chicks. They were randomly distributed into 4 dietary treatments (T1, T2, T3 and T4 supplemented with Eugenia jambolana and Psidium guajava leaf meal mixture (LMM) @ 0, 2.5, 5.0 and 7.5 % of diet, respectively) of 30 birds per treatment, each having 3 replicates (10 chicks / replicate) in a complete randomized block design. Feed intake (g) in 0-3, 4-6 and 0-6 weeks were significantly (P<0.05) higher in T1 followed by T2, T3 and least in T4 groups. Weight gain (g) in 0-3, 4-6 and 0-6 weeks of broiler chicks were significantly higher in T1 as compared to T2, T3 and T4 groups. FCR of 0-3 weeks among groups was statistically non significant (P<0.05), while, at 4-6 weeks, it was found to be lowest in T4, whereas, in 0-6 weeks was significantly (P<0.05) lower in T1 than that of other groups. LMM supplementation comparatively depress (P<0.068) average body weight during metabolism trial in T4 than that of T1 group. Apparent digestibility (%) of dry matter, crude protein and crude fibre were significantly (P<0.05) lower, while digestibilities of organic matter, ether extract and nitrogen free extract were comparatively lower in T4 than that of T1, T2 and T3. Moreover, nitrogen (N) intake and retention were significantly (P<0.05) lower and N excretion was significantly higher in T3 and T4 than that of T1 and T2. Mean haemoglobin and packed cell volume were significantly higher in T1 and T2 than that of T3 and T4. The LMM supplemented groups showed better antioxidant indices, cell mediated and humoral immune responses compared to control. It was concluded that LMM supplementation (2.5% or even 5%) improved antioxidant status, immune response and maintaining nutrient intake and utilization.